Outcomes and Prognosis Factors in Patients With Vena Cava Filters in a Quaternary Medical Center: A 5-Year Retrospective Analysis. (March 2021) - Elias, Michael; Elias, Antoine; Oropello, John; Doucette, John; Jebakumar, Jebakaran; Kohli-Seth, Roopa
Background: Indications for inferior vena cava filter (IVCF) placement are controversial. This study assesses the proportion of different indications for IVCF placement and the associated 30-day event rates and predictors for all-cause mortality, deep vein thrombosis (DVT), pulmonary embolism, and bleeding after IVCF placement. Method: In this 5-year retrospective cohort observational study in a quaternary care center, consecutive patients with IVCF placement were identified through cross-matching of 3 database sets and classified into 3 indication groups defined as "standard" in patients with venous thromboembolism (VTE) and contraindication to anticoagulants, "extended" in patients with VTE but no contraindication to anticoagulants, and "prophylactic" in patients without VTE. Results: We identified 1248 IVCF placements, that is, 238 (19.1%) IVCF placements for standard indications, 583 (46.7%) IVCF placements for extended indications, and 427 (34.2%) IVCF placements for prophylactic indications. Deep vein thrombosis rates [95% confidence interval] were higher in the extended (8.06% [5.98-10.58]) and prophylactic (7.73% [5.38-10.68]) groups than in the standard group (3.36% [1.46-6.52]). Mortality rates were higher in the standard group (12.18% [8.31-17.03]) than in the extended group (7.55% [5.54-9.99]) and the prophylactic (5.85% [3.82-8.52]) group. Bleeding rates were higher in the standard group (4.62% [2.33-8.12]) than in the prophylactic group (2.11% [0.97-3.96]). Best predictors for VTE were acute medical conditions; best predictors for mortality were age, acute medical conditions, cancer, and Medicare health insurance. Conclusions: Prophylactic and extended indications account for the majority of IVCF placements. The standard indication is associated with the lowest VTE rate that may be explained by the competing risk of mortality higher in this group and related to the underlying medical conditions and bleeding risk. In the prophylactic group (no VTE at baseline), the exceedingly high DVT rate may be related to the IVCF placement.